High-performance titanosilicate catalyst obtained through combination of liquid-phase and solid-phase transformation mechanisms - Wang, Jingui (2014)
A novel strategy for the synthesis of microporous crystalline titanosilicate catalyst (TS-1) was developed based on the combination of liquid-phase and solid-phase transformation mechanisms. The core concept of this strategy was to crystallize the mixed precursors composed of both liquid-phase and solid-phase precursors. The anionic polyelectrolyte poly(acrylic acid) was used as a unique gelating agent to prepare the solid/liquid mixture, which can partly convert the liquid-phase precursor to the solid-phase precursor. Active framework Ti was formed by in situ conversion of the Ti species from the solid-phase precursor during the crystallization stage, as well as by the transfer of Ti species from the liquid-phase precursor to the solid crystal after the crystallization. In this way, the content of active Ti in TS-1 was significantly increased. The obtained product displayed high activity for the oxidation reaction of n-hexane and 1-hexene.